Optimization of Bhabinkamtibmas Polres Sukoharjo to Reduce Public Distrust Against Polri at Polres Sukoharjo - Fadilah, Muhammad Hafizh (Advances in Police Science Research Journal, 2024)
As stated in Article 5 paragraph (1) of Law Number 2 of 2002 concerning the Indonesian National Police, the Police are a tool of the State which has the main task of maintaining public security and order, upholding the law, and providing protection, protection, and service to the community in order to maintain internal security. So it is fitting for the Police to get a good title in the eyes of the community. However, currently, the Police are facing a wave of public distrust caused by several factors, such as poor service, unprofessional law enforcement, and bad behavior by members of the Police. The Bhabinkamtibmas, as the bearer of the Polmas in the village, have also been affected by this condition. This research was carried out to describe and explore the duties, functions, and powers of the Bhabinkamtibmas Polres Sukoharjo to reduce public distrust towards the Police and describe the inhibiting and supporting factors for the ability of Bhabinkamtibmas in reducing public distrust of the Police at the Sukoharjo Polres. This research uses field research supported by library research (library). The data collection technique uses interview techniques, observation (observation), and document study. The analysis technique used in this study is first collecting, then reducing data, then presenting data, and ending with drawing conclusions. Theories used in this study include management theory, SWOT theory, and perceived behavioral control theory. The results showed that the general level of public trust in the Sukoharjo District Police was quite good. However, if it is investigated again, only the Public Service indicators are rated as Good, while the Law Enforcement and Member Behavior indicators receive a poor rating. So efforts are still needed to improve it.